1-(4-Bromophenyl)-2-{5-[(3,5-dimethyl-1H-pyrazol-1-yl)methyl]-4-phenyl-4H-1,2,4-triazol-3-ylsulfanyl}ethanone - Shan-Mei Xiao (Acta Crystallographica Section E, 2009)
The title compound, C22H20BrN5OS, is a potent new fungicide. The planes of the phenyl and pyrozole rings are almost perpendicular, making a dihedral angle of 86.5 (4)°. There are two non-classical intermolecular C—H...O and C—H...N hydrogen bonds in the crystal structure.